Smoking and projected cardiovascular risk in an HIV‐positive Asian regional cohort. Issue 7 (19th July 2016) - Do, TC; Boettiger, D; Law, M; Pujari, S; Zhang, F; Chaiwarith, R; Kiertiburanakul, S; Lee, MP; Ditangco, R; Wong, WW; Nguyen, KV; Merati, TP; et al.
Abstract : Objectives: The aim of the study was to assess the prevalence and characteristics associated with current smoking in an Asian HIV‐positive cohort, to calculate the predictive risks of cardiovascular disease (CVD), coronary heart disease (CHD) and myocardial infarction (MI), and to identify the impact that simulated interventions may have. Methods: Logistic regression analysis was used to distinguish associated current smoking characteristics. Five‐year predictive risks of CVD, CHD and MI and the impact of simulated interventions were calculated utilizing the Data Collection on Adverse Effects of Anti‐HIV Drugs Study (D:A:D) algorithm. Results: Smoking status data were collected from 4274 participants and 1496 of these had sufficient data for simulated intervention calculations. Current smoking prevalence in these two groups was similar (23.2% vs . 19.9%, respectively). Characteristics associated with current smoking included age>  50 years compared with 30–39 years [odds ratio (OR) 0.65; 95% confidence interval (CI) 0.51–0.83], HIV exposure through injecting drug use compared with heterosexual exposure (OR 3.03; 95% CI 2.25–4.07), and receiving antiretroviral therapy (ART) at study sites in Singapore, South Korea, Malaysia, Japan and Vietnam in comparison to Thailand (all OR > 2). Women were less likely to smoke than men (OR 0.11; 95% CI 0.08–0.14). In simulated interventions, smoking cessation demonstrated the greatest impact in reducing CVD and CHD risk and closely approximated the impact of switching from abacavir to an alternate antiretroviral in the reduction of 5‐year MI risk. Conclusions: Multiple interventions could reduce CVD, CHD and MI risk in Asian HIV‐positive patients, with smoking cessation potentially being the most influential.